Medical Journal of Indonesia Vol.26. Issue 3, September 2017, pp 167-236 - Redaksi (Universitas 'Aisyiyah Yk, 2017)
- The effects of quercetin on oxidative stress and fibrosis markers in chronic kidney disease rat model - Knock-out transmembrane prostate androgen-induced protein gene suppressed triple-negative breast cancer cell proliferation - ...